Influence of the amorphous phase and preceding solution processing on the eutectic behaviour in the state diagram of P3HT : PC61BM determined by rapid heat–cool calorimetry. Issue 95 (28th September 2016) - Defour, M.; Van den Brande, N.; Van Lokeren, L.; Van Assche, G.; Maes, W.; Vanderzande, D.; Van Mele, B.
Abstract : Experimental determination of eutectic state diagrams for organic photovoltaics based on advanced calorimetry highlighting the importance of the amorphous phase. Abstract : Rapid heat–cool calorimetry was used to determine the state diagram of P3HT : PC61 BM mixtures. A particular focus was given to the determination of the eutectic composition and temperature. P3HT was fractionated in three different narrow molecular weight fractions (14.9 kg mol −1, 32.4 kg mol −1, 89.1 kg mol −1 ) in order to study its effect on the eutectic behaviour. Heating rates of 500 K min −1 were utilised to drastically decrease or suppress cold crystallization of the mixtures, especially around the eutectic composition. This led to a more accurate determination of the state diagram. An important decrease of crystallization kinetics was observed around the eutectic composition, making an accurate determination difficult. This was shown to be due to the melting (and crystallization) temperature depression around the eutectic composition coupled with the vitrification of PC61 BM at 139 °C. These findings highlight the importance of the amorphous phase for the morphology development of the active layer in organic photovoltaics. By changing the preceding sample solution preparation and by using dedicated cooling and heating rates, the eutectic composition was found between 50–55 wt% PC61 BM for 14.9 kg mol −1 P3HT, 55–60 wt% PC61 BM for 32.4 kg mol −1 P3HT, and 55–65 wt% PC61 BM for 89.1 kg mol −1 P3HT. The eutectic onset temperature of melting was found to be around 140 °C for the different P3HT molecular weight fractions, which is close to the glass transition of pure PC61 BM.